Preliminary results of chemical analysis of sow colostrum from first to ninth parity - Budimir, Kristina; Čuljak, Križan; Kušec, Goran; Margeta, Vladimir (Acta Agraria Kaposváriensis, 2014)
Chemical composition and quality of colostrum have a great influence on pigs’ lifetime productivity and pre-weaning mortality. There are a different methods for determinate quality of colostrum, but some of them are not suitable for use at the farms. Method for assessing the quality of colostrum should be quick, simple and accurate. In today’s intensive keeping condition pre-weaning period is the most sensitive and the highest losses of piglets are in that period of production. Quality of colostrum is the factor which has an influence on the decrease of that mortality. Research was conducted on 90 samples of colostrum collected from 33 PIC sows. Samples was collected regarding the parity (first, third and ninth) and time of the year (spring, summer and winter). The objective of this study was to examine the changes in fat, protein, lactose, dry matter (DM) and non-fat dry matter (NDF) amount in sows’ milk regarding the number of parity and season as well as determining the quality of colostrum using the refractometry method.